Native Forests Show Resilience to Selective Timber Harvesting in Southeast Queensland, Australia - Neumann, Mathias; Adams, Mark A.; Lewis, Tom (Frontiers in Forests and Global Change, 2021)
There is little published information on effects of management on the structure of mixed species forests in Queensland, Australia. We used long-term growth, abundance and dimension data from permanent plots to test the hypothesis that harvesting would reduce numbers of large trees and growth increments, while increasing recruitment. This hypothesis is key to policy and management decisions for forests covering about 9.5 million hectares. Inclusion of data on changes in forest structure (e.g., tree diameter, stem density) helps in assessment of forest suitability as habitat for a range of species. Growth rate (basal area) varied widely among forest types. Growth of each of four key species (i.e., Eucalyptus pilularis, Corymbia citriodora ssp. variegata, Callitris glaucophylla, and Eucalyptus crebra) reflected variation in rainfall across the study region. Callitris glaucophylla, a native conifer, is dominant when rainfall is < 600 mm per year. Corymbia citriodora ssp. variegata grows across much wider ranges in rainfall (600–1,200 mm year–1) at rates similar to Callitris glaucophylla. Historic harvesting increased recruitment and also increased the symmetry of diameter distributions. Harvesting has not reduced the current density of larger trees (diameter at breast height, DBH ≥ 60 cm) at a regional scale. Stand growth was unaffected by management principally owing to an increase in the density of trees of smaller diameter (10–20 cm DBH). Self-thinning limits potential stocking and we tested 3 methods for predicting self-thinning across forest types. We found that the slope of self-thinning lines under drier conditions is mostly < –2, suggesting highly dynamic self-thinning. Using a species-boundary line approach, growth is predicted to slow when basal areas reach around 66.1 m2 ha–1 in E. pilularis, 19.0 m2 ha–1 in C. citriodora ssp. variegata, 16.5 m2 ha–1 in Callitris glaucophylla, and 14.2 m2 ha–1 in E. crebra. The slope of the self-thinning line for E. pilularis was –1.662, similar to Reineke’s Stand Density Index (slope –1.605). To date, there is little evidence that selective harvesting and thinning have had negative impacts on rates of growth, on timber production, carbon sequestration or on aspects of forest structure regarded as important for biodiversity.